Analysis of the Linker Region Joining the Adenylation and Carrier Protein Domains of the Modular Non-Ribosomal Peptide Synthetases - Miller, Bradley R. (2014)
Non-Ribosomal Peptide Synthetases (NRPSs) are multi-modular proteins capable of producing important peptide natural products. Using an assembly-line process the amino acid substrate and peptide intermediates are passed between the active sites of different catalytic domains of the NRPS while bound covalently to a peptidyl carrier protein (PCP) domain. Examination of the linker sequences that join the NRPS adenylation and PCP domains identified several conserved proline residues that are not found in standalone adenylation domains. We examined the roles of these proline residues and neighboring conserved sequences through mutagenesis and biochemical analysis of the reaction catalyzed by the adenylation domain and the fully reconstituted NRPS pathway. In particular, we identified a conserved LPxP motif at the start of the adenylation-PCP linker. The LPxP motif interacts with a region on the adenylation domain to stabilize a critical catalytic lysine residue belonging to the A10 motif that immediately precedes the linker. Further, this interaction with the C-terminal sub-domain of the adenylation domain may coordinate movement of the PCP with the conformational change of the adenylation domain. Through this work, we extend the conserved A10 motif of the adenylation domain and identify residues that enable proper adenylation domain function.